Consensuality : Didier Anzieu, gender and the sense of touch - Segal, Naomi (Genus--gender in modern culture ;, 2009)
The body is an emissary. We know little of our own feelings or the feelings of others, but that ignorance is mediated through our organ of touch, the skin. The term 'consensuality' stands for the co-presence of perceptions on the skin, which is the backcloth to sensation and thought. If the intelligence of the body is the basis of both sense and consent, consensuality also has to do with human relations based on the sense of touch, particularly the mother-child couple and the relation of desire, love and loss. This book touches on a range of cultural figures including Gide, Princess Diana, Kaf.